Screening for aroma in rice genotypes with African and Asian backgrounds - Ndikuryayo, Cyprien; Ndayiragije, Alexis; Kilasi, Newton; Kusolwa, Paul (Wiley, 2023)
Aromatic rice is highly preferred by consumers and has an important market worldwide. The demand for aromatic rice is high in East African countries, mainly in urban areas. Among the rice varieties that are grown in Burundi, few of them have a slight aroma which is not enough to satisfy the consumers’ demand and preference. There is no published report on the status of aroma in locally grown varieties and breeding lines in Burundi yet. This study aimed to identify aromatic genotypes that can be used in the breeding program to meet preferences of consumers. Two hundred fifteen genotypes were subjected to kompetitive allele-specific PCR genotyping and sensory evaluation methods. Fifty-three genotypes had the betaine aldehyde dehydrogenase (BADH2) gene for fragrance and displayed different levels of aroma expression. The sensory evaluation revealed two strongly aromatic genotypes, 43 moderately aromatic genotypes, 131 slightly aromatic genotypes, and 32 nonaromatic genotypes.The results of this study showed that BADH2 gene is significantly associated with rice aroma in accordance with previous reports. Furthermore, aroma and taste were positively and significantly correlated. Strongly aromatic genotypes (SUPA KATRIN and SUPA DE NYANZA –LAC) having the BADH2 gene for fragrance are of great interest for use in the breeding program to improve rice varieties to meet consumers' preferences in Burundi.